Prevalencia de hipotiroidismo y factores de riesgo relacionados en personas adultas atendidos en el Hospital Alfredo Noboa Montenegro, octubre 2018 – abril 2019 - Montero Ruiz, Gladys Magdalena (2019)
Hypothyroidism is a pathology that can be present in people of any age and is characterized by low levels of thyroid hormones in the blood. That is why the present research work aimed to determine the prevalence of hypothyroidism by analyzing the results of thyroid profile tests performed on adults who attended the Ambato General Teaching Hospital during the period May 2017 - June 2018. The development of the same, a non-experimental, descriptive, cross-sectional and quantitative approach research was proposed, in which the study population was made up of 914 results, which were statistically analyzed in the SPSS program, version 24, creating tables with information about the presence of the pathology, the type of hypothyroidism and a comparison between the age and gender of the hypothyroid patients. The analysis of the results was performed in women of 47.52 ± 16.19 years and in men of 49.75 ± 18.96 years, resulting in 306 people 33.6% with hypothyroidism, of which 219 data 71, 6% indicated that subclinical hypothyroidism is the most frequent. In addition, it was observed that 249 women (81.4%) had a deficit of thyroid hormones and finally it was demonstrated that 148 adults between 41 to 65 years (48.4%) presented the pathology under study. Finally, it was concluded that the prevalence of hypothyroidism in the study population was 3.6% and that adult female patients presented a higher percentage of the pathology.